The Paradox of Civil Policing in Contemporary South Africa. Issue 2 (July 2017) - Nyawasha, Tawanda Sydesky; Mokhahlane, Phakiso Michael
This article is a study of democratic policing in contemporary South Africa. The attempt in this article is to offer a scholarly analysis on the nature of civil policing in South Africa. Empirically, our focus is on everyday observations and also public discourse shaped and transmitted within the civil and political realms of the broader South African community. We argue that civil policing and security in South Africa is typified by a paradox that destroys the civic virtue and rationale of policing. It is our argument also that this paradox has posed a significant challenge to democratic and civil policing in a new South Africa. The solution to this paradox, we will argue, lies in recognising policing and security as uniquely constituted 'public goods'. We also argue for a rethink on the place of culture in the policing register and grammar of post-apartheid South Africa. In this article, our treatment of civil policing and its challenges in South Africa is informed by recent incidences that have shown an imbrication between violence and the repertoires of policing. Overall, we contend that policing in contemporary South Africa sits at the disjuncture between political liberation and the persistent use of physical force. In all the cases, we shall refer to in this article, we will attempt to show how policing has often been entirely extricated from the habitus of law.